A molecular electron density theory study of the enhanced reactivity of aza aromatic compounds participating in Diels–Alder reactions. Issue 2 (17th December 2019) - Domingo, Luis R.; Ríos-Gutiérrez, Mar; Pérez, Patricia
Abstract : The change of C–H by N: in these aromatic compounds decreases the ring electron density (RED), thus decreasing the activation energies of the aza Diels–Alder reactions mainly by the loss of the aromatic character of the reagents. Abstract : The enhanced reactivity of a series of four aza aromatic compounds (AACs) participating in the Diels–Alder (DA) reactions with ethylene has been studied using Molecular Electron Density Theory (MEDT). The analysis of the electronic structure of these AACs allows establishing that the substitution of the C–H unity by the isoelectronic N: unity linearly decreases the ring electron density (RED) of these compounds and concomitantly decreases their aromatic character and increases their electrophilic character. These behaviours not only decrease drastically the activation energies of these DA reactions, but also increase the reaction energies when they are compared with the very unfavourable DA reaction between benzene and ethylene. Very good correlations between the NICS(0) values and the electrophilicity ω indices of these AACs with the RED values are found. The present MEDT study makes it possible to establish two empirical electron density unity (EDU) indices accounting for the contribution of the 〉C and 〉N unities, 2.77 and 2.19 e, respectively, for the RED, which is mainly responsible for the reactivity of these AACs. Comprehensive chemical concepts such as electron density, aromaticity and electrophilicity make it possible to explain the chemical reactivity of these AACs participating in DA reactions towards ethylene.